2000
DOI: 10.7164/antibiotics.53.144
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterisation of Disruptants of the Streptomyces coelicolor A3(2). ActVI Genes Involved in Actinorhodin Biosynthesis.

Abstract: The actVl genetic region ofStreptomyces coelicolor A3(2) is part of the biosynthetic gene cluster of actinorhodin (ACT), the act cluster, consisting of six ORFs: ORFB, ORFA, ORF1, ORF2, ORF3, ORF4. A newly devised method of ACTdetection with a combination of HPLC and LC/MSwas applied to the analysis of the disruptants of each OREACTwas produced by those of ORFB, ORFA, ORF3, and ORF4. Instead of ACT, the ORF1disruptant produced 3,8-dihydroxy-l -methylanthraquinone-2-carboxylic acid (DMAC)and aloesaponarin II as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 27 publications
(3 reference statements)
3
65
0
Order By: Relevance
“…Genome integration was confirmed by colony PCR with the primer set Neo-F and Neo-R for kanamycin-resistant clones as described by Ishikawa et al (2000). Transformants were liquid-cultured as described previously (Taguchi et al, 2000a). The medium separated from the broth by centrifugation was directly subjected to reversed-phase HPLC analysis on a TOSOH 8020 system under the following conditions: column, TSK gel ODS-80TM (4?6 mm i.d.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Genome integration was confirmed by colony PCR with the primer set Neo-F and Neo-R for kanamycin-resistant clones as described by Ishikawa et al (2000). Transformants were liquid-cultured as described previously (Taguchi et al, 2000a). The medium separated from the broth by centrifugation was directly subjected to reversed-phase HPLC analysis on a TOSOH 8020 system under the following conditions: column, TSK gel ODS-80TM (4?6 mm i.d.…”
Section: Methodsmentioning
confidence: 99%
“…3). Our earlier experiments (Taguchi et al, 2000a) suggested the actVI-ORF2 protein, an enoyl reductase homologue, to function as the second reductase at C-15 to complete the (3S, 15R) configuration. The presence of another homologue, actVI-ORF4, prompted us to propose that the product might assist an unusual mode of reduction of (S)-DNPA (Taguchi et al, 2000a).…”
Section: Post-pks Tailoring Steps In Aglycone Formationmentioning
confidence: 96%
See 2 more Smart Citations
“…3) which are often found in experiments with streptomycetes mutants bearing manipulations in the cyclase functions of type II polyketide synthases (PKS) [6,7] and are under ongoing investigations [8]. In these experiments 2 and 3 turned out to be important key metabolites for the elucidation of the biosynthetic pathway of 4.…”
mentioning
confidence: 99%